Kā latviski pareizāk atveidot Ἀπόστολος Παῦλος? - Zeps, Dainis (My University, 2016)
Article considers how to translate into Latvian the proper name of Ἀπόστολος Παῦλος in New Testament, either Pāvils or Pauls. The first case is chosen by tradition, but author argues that the second choice is more in correspondence with how Greek word Παῦλος would be rendered into Latvian.
How to render in Latvian Ἀπόστολος Παῦλος?
Keywords: Research Subject Categories::HUMANITIES and RELIGION::Religion/Theology; Greek New testament; Proper names; Latvian translation